OP0136 BCL-2 As a Potential Therapeutic Target in Human Lupus Tubulointerstitial Inflammation. (9th June 2015) - Wang, L.C.; Ko, K.; Yanez, D.; Kaverina, N.; Liarski, V.M.; Peng, Y.; Lan, L.; Perper, S.; Schwartz, A.; O'Connor, L.; Souers, A.; Elmore, S.; et al.
Abstract : Background: Lupus nephritis (LuN) is the most common, severe manifestation of systemic lupus erythematosus (SLE). We have previously shown that glomerulonephritis appears to be a manifestation of systemic autoimmunity while tubulointerstitial inflammation (TII) is associated with additional, in situ adaptive immune cell networks that might amplify local inflammation and tissue damage. Furthermore, patients with significant TII are more likely to fail conventional therapy and progress to renal failure. Therefore, understanding the mechanisms of in situ adaptive immunity in lupus TII might provide new therapeutic opportunities for treating LuN. In mice, BCL-2 family proteins are key regulators of immune cell apoptosis and forced expression of BCL-2 in B cells promotes a lupus-like nephritis. We hypothesized that dysregulated expression of the BCL-2 family proteins in human LuN TII might contribute to local adaptive immunity, inflammation and disease pathogenesis. Objectives: To determine the expression of BCL2 family proteins in human LuN TII. Methods: Frozen renal biopsy specimens from 26 patients with SLE (ISN/RPS Class III, IV or V LuN), 10 mixed cellular renal allograft rejection (MR) biopsy specimens and tonsil samples from healthy subjects were stained with antibodies specific for CD20, CD4, BCL-2, MCL-1 or BIM. Images were acquired using scanning laser confocal microscopy. IFNa-induced NZB/W F1 mice were treated daily with vehicle or 30 mg/kg of Venetoclax (ABT-199), a BCL-2 selective inhibitor, and analyzed for survival and the development of proteinuria. Results: A recently developed imaging tool ( Science Translational Medicine 2014, 6:230) was used to quantify the frequency of CD20 + B and CD4 + T cells expressing the anti-apoptotic molecules BCL-2, MCL-1 and the pro-apoptotic molecule BIM. In primary follicles of normal tonsils, both B and T cells frequently expressed BCL-2. However, upon entry into germinal centers (GC), BCL-2 was down-regulated and MCL-1 was induced. In marked contrast, in LuN and MR TII biopsies, the frequency of BCL-2 + cells was increased in B and T cells while MCL-1 + cells were rare. Observed differences between tonsil GC lymphocytes versus TII in LuN and MR for both BCL-2 and MCL-1 were highly significant (p<0.001). These expression differences were confirmed by laser capture microscopy coupled to qPCR. In contrast, the frequency of BIM + cells did not significantly vary among tissues. Consistent with these findings, BCL-2, but not MCL-1 expressing cells were detected in the inflamed kidney in IFNa-induced NZB/W F1 lupus mice. Furthermore, administration of Venetoclax, prevented the development of lupus nephritis in these animals. Conclusions: Frequent BCL-2 expressing cells were present in LuN, MR TII tissues and IFNa-induced NZB/W F1 lupus mice. Treatment of these mice with Venetoclax resulted in the preservation of renal function. These data indicate that BCL-2, which is dysregulated in TII, is an attractive therapeutic target in cases of lupus nephritis manifesting tubulointerstitial inflammation. Disclosure of Interest: L. C. Wang Shareholder of: Abbvie Inc., K. Ko: None declared, D. Yanez: None declared, N. Kaverina: None declared, V. Liarski: None declared, Y. Peng: None declared, L. Lan: None declared, S. Perper Shareholder of: Abbvie Inc., A. Schwartz Shareholder of: Abbvie Inc., L. O'Connor Shareholder of: Abbvie Inc., A. Souers Shareholder of: Abbvie Inc., S. Elmore Shareholder of: Abbvie Inc., L. Olson Shareholder of: Abbvie Inc., M. Giger: None declared, M. Clark Grant/research support from: Abbvie Inc.